The exercise of empathetic leadership at universities - Marcellus Forh Mbah; Sara Zara Milani; Iryna Kushnir (Cogent Education)
This article delves into the manifestation of empathetic leadership in relation to war-affected communities in the context of the UK’s higher education institutions. Grounded in the theoretical frameworks of universality and the ecological university, the qualitative study employed a thematic analysis of statements from a random selection of university leaders responding to the Ukraine–Russia war. The analysis reveals a dual-dimensional approach to empathetic leadership, encompassing expression and action. Leaders express empathy by 1) acknowledging the severity of the situation, and 2) assertion to support their community who are affected by the war. The expressive dimensions serve as initial signals to ensuing actions. While these actions, addressing immediate needs, also align with the principles of the ecological university, a comprehensive continuum of empathetic leadership has been proposed. This article’s original contribution hinges on the broad understanding of empathetic leadership, with a contextual focus on the university during a defining moment of an emergency or crisis such as war. It heightens the need for further studies on the idea of the university and its internal and wider responsibilities in a changing global landscape, sometimes characterised by conflicts, epidemics, pandemics, and other challenges brought to its shore by forces beyond its control.